THE REVOLUTION IN ACCOUNTING. - Corbin, Donald A. (The Accounting Review, 1962)
The article discusses the revolution in the area of accounting which gives the beginners a firm foundation upon which to build a consistent, meaningful structure of accounting theory. Primarily, the "revolution" involves a willingness, whenever necessary, to modify the orthodox historical cost and realization "principles" of accounting. In addition to emphasizing the forward-looking aspects of accounting, a complete revolution will emphasize the importance of economic theory, historical accounting development, and a consistent theoretical construct. The utility of using the economists' forward-looking approach, when prices rise as well as when they fall, must be compared with the difficulties and possible errors of so-doing. Bases for a rational choice of methods, however, will have been developed. Choice will no longer have to be made solely on the basis of custom or reference to authority. The accountant, hopefully, will be prepared with an independent, analytical, approach to solving important accounting problems. A host of decisions, not just managerial decisions, may then be made by various groups in society, based on relevant data and sound, consistent accounting theory.